Pandemics, public-private partnerships (PPPs), and force majeure | COVID-19 expectations and implications. Issue 12 (1st December 2020) - Casady, Carter B.; Baxter, David
Abstract: The novel coronavirus (COVID-19) pandemic is placing unprecedented stress on public-private partnerships (PPPs), creating the real possibility of widespread project failures. The disruption and potential collapse of multiple PPP projects will likely trigger force majeure contractual provisions, but the applicability and efficacy of these generic catch-all clauses remain in question. This critical note therefore discusses the implications of force majeure contractual conditions on PPPs in the COVID-19 epoch. We first define the concept of force majeure as it pertains to pandemics. Next, we review a select number of international policies for such events, outlining their key features and glaring shortcomings. Then, we use Novia Scotia's Highway 104 Twinning Project as an illustrative case example of improved force majeure risk management. Finally, after reflecting on the three ironies of construction crisis management, we outline the need for swift trust in PPPs during this current pandemic and conclude by calling for a comprehensive revision of force majeure contract provisions.